Interaction of Mason-Pfizer monkey virus matrix protein with plasma membrane - Prchal, Jan; Kroupa, Tomáš; Ruml, Tomáš; Hrabal, Richard (Frontiers in microbiology, 2013)
Budding is the final step of the late phase of retroviral life cycle. It begins with the interaction of Gag precursor with plasma membrane (PM) through its N-terminal domain, the matrix protein (MA). However, single genera of Retroviridae family differ in the way how they interact with PM. While in case of Lentiviruses (e.g., human immunodeficiency virus) the structural polyprotein precursor Gag interacts with cellular membrane prior to the assembly, Betaretroviruses [Mason-Pfizer monkey virus (M-PMV)] first assemble their virus-like particles (VLPs) in the pericentriolar region of the infected cell and therefore, already assembled particles interact with the membrane. Although both these types of retroviruses use similar mechanism of the interaction of Gag with the membrane, the difference in the site of assembly leads to some differences in the mechanism of the interaction. Here we describe the interaction of M-PMV MA with PM with emphasis on the structural aspects of the interaction with single phospholipids.
Keywords: interaction; matrix protein; Mason-Pfizer monkey virus; phospholipids; Retrovirus; plasma membrane